Hubungan Kecenderungan Body Dysmorphic Disorder (BDD) dan Intensitas Penggunaan Instagram pada Perempuan Dewasa Awal Pengakses Konten Kecantikan Instagram di DKI Jakarta - Kania Pratiwi; Laurentius Sandi Witarso (INADA, 2025)
Instagram plays a role in shaping beauty perceptions through its features and content. Intensive use of Instagram is associated with tendencies towards BDD, such as the internalization of beauty standards and social comparison. This study focuses on early adult women who access beauty-related content on Instagram and reside in DKI Jakarta. Although numeroues studies have linked social media use with aspects of body image, few have specifically examined the relationship between BDD tendencies and Instagram usage intensity within this particular demographic. This research aims to investigate the correlation between BDD tendencies and Instagram usage intensity among early adult women accessing beauty content on Instagram in DKI Jakarta. This study used a quantitative method using the Spearman-Brown correlation technique. BDD tendencies were measured using a scale adapted from aspects of BDD developed by Rosen and Reiter (1996). Instagram usage intensity was measured using an instrument adapted from Ellison et al.’s (2007) Facebook Intensity Scale. A total of 140 participants, all early adult women who access beauty-related content on Instagram and live in DKI Jakarta, were involved in this study. The results show a significant positive correlation (r2 = 0,045, p<.05) between BDD tendencies and Instagram usage intensity among early adult women accessing beauty content on Instagram in DKI Jakarta. This study is expected to contribute to the growing body of knowledge and increase awareness, particularly regarding Instagram use and the tendency toward BDD.